2012
DOI: 10.2174/187152912801823138
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genetic Factors in Statins Side-Effects

Abstract: Statins are relevant drugs involved in the reduction of cardiovascular events both in primary and secondary prevention. Related muscular side-effects are the most common cause of withdrawal and statins discontinuation could induce a negative rebound effect in terms of vascular events. Among factors in association with statins side-effects the combination with other drugs and the female sex are established conditions. However recent data suggest a specific genetic influence in intolerance development, at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…All patients were of Croatian ancestry. Median (interquartile range) age was 56 (48-66) and 60 (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) in the groups of patients with and without ADRs, respectively. The gender distribution was identical, and atorvastatin median prescribed dose was the same in both groups.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were of Croatian ancestry. Median (interquartile range) age was 56 (48-66) and 60 (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) in the groups of patients with and without ADRs, respectively. The gender distribution was identical, and atorvastatin median prescribed dose was the same in both groups.…”
Section: Subjectsmentioning
confidence: 99%
“…For patients at an increased risk of cardiovascular disease (CVD) who have been prescribed statins, it is crucial to be compliant with their therapy. Statin-related muscular side effects are the most common cause of withdrawal and statin discontinuation could induce increased vascular events [57]. Currently there is no direct clinical evidence that the personalized prescribing of statins using genotyping will improve patients' medication adherence; however, previous analyses suggest that this is a logical conclusion [58].…”
Section: Probability Of Adr (%)mentioning
confidence: 99%
“…Genome‐wide association study has identified SNPs relevant to the management of other cardiovascular diseases . Candidate gene studies are intrinsically limited.…”
Section: Novel Positional Candidates (Discovered Through Gwas)mentioning
confidence: 99%
“…Genome wide association studies (GWAS) provide a mechanism for discovering relevant genetic loci and have identified drug-gene interactions in treatment of other cardiovascular diseases (61)(62). To date virtually no published GWAS has sought relevant genes in HF drug response, GWAS have been used to identify loci implicated in the development of HF and outcome in patients with HF (63-65).…”
Section: Novel Positional Candidates: Discovered Through Gwasmentioning
confidence: 99%